2003
DOI: 10.1139/g02-125
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTL for yield components, vigor, and resistance toPhytophthora palmivorainTheobroma cacaoL.

Abstract: Quantitative trait loci (QTL) mapping for agronomic traits was carried out in cocoa (Theobroma cacao L.). Regions of the genome involved in yield, vigor, and resistance to Phytophthora palmivora were identified. Three heterozygous clones, one upper Amazon Forastero (IMC78) and two Trinitario (DR1 and S52), were crossed with the same male parent, a lower Amazon Forastero (Catongo), known to be highly homozygous. Observations were made on progeny over nine consecutive years. One to three QTL related to yield wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 23 publications
(16 reference statements)
4
34
0
Order By: Relevance
“…These SSRs were already useful tools for the identification of QTLs related to morphological or disease resistance traits (Crouzillat et al 2000;Flament et al 2001;Risterucci et al 2003;Clement et al 2003;Queiroz et al 2003;Brown et al 2007;Brown et al 2005). The high level of polymorphism for these SSR markers also helped to create a composite map by mapping SSRs (bridge markers) common to three different maps , and led to the establishment of a consensus map derived from ten different progenies, which has enabled a meta-analysis of QTLs related to resistance traits in cocoa (Lanaud et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These SSRs were already useful tools for the identification of QTLs related to morphological or disease resistance traits (Crouzillat et al 2000;Flament et al 2001;Risterucci et al 2003;Clement et al 2003;Queiroz et al 2003;Brown et al 2007;Brown et al 2005). The high level of polymorphism for these SSR markers also helped to create a composite map by mapping SSRs (bridge markers) common to three different maps , and led to the establishment of a consensus map derived from ten different progenies, which has enabled a meta-analysis of QTLs related to resistance traits in cocoa (Lanaud et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several regions of the genome involved in yield components and Phytophthora spp. resistance were identified (Crouzillat et al 2000;Flament et al 2001;Lanaud et al 2002;ClØment et al 2003aClØment et al , 2003bRisterucci et al 2003) and confirmed the polygenic nature of this quantitative resistance in cocoa. A region of chromosome 6 appears particularly interesting and gave QTL for yield components and resistance to Phytophthora.…”
Section: Introductionmentioning
confidence: 83%
“…Recently, both RGAs and defence gene analogues (DGA) were isolated from cocoa genomic DNA using degenerate primers designed from conserved domains of several plant resistance and defence genes including the NBS motif (Kuhn et al 2003, present in a number of resistance genes such as the tobacco N; the STK (serine/threonine kinases) subdomains of plants such as the Pto tomato gene; and conserved domains of two defence gene families, the pathogenesis-related proteins (PR) of classes 2 and 5 ). Most of the RGA and PR2-DGA clones, isolated by Lanaud et al (2004), were mapped in a segregating population and co-localizations were observed between some RGA and DGA, and QTL for resistance to Phytophthora previously identified in several progenies (Crouzillat et al 2000, Lanaud et al 2002, ClØment et al 2003bRisterucci et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we used co-dominant markers (SSRs) to facilitate both the map construction and QTL detection (Van Ooijen 2006;Van Ooijen 2009;Jourjon et al 2005). This type of approach was proved to be successful in other plant species (Clement et al 2003;Souza et al 2013). In our study, the two bi-parental maps were similar for both genetic map sizes and number of loci mapped.…”
Section: Genetic Map Constructionmentioning
confidence: 99%